Forming Students' Interest In Library Culture - Umarkulova Kamola Begalievna (Zien Journals, 2023)
It will be possible to develop effective options for the content of the process of formation of interest in samples in the development of reading culture among students and development of reading culture among students.
Keywords: interest; Scientific and technical models; Game models; Simulation models